2016
DOI: 10.1097/j.pain.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of pain-related functional brain connectivity compared with pain self-report

Abstract: Test-retest reliability, or reproducibility of results over time, is poorly established for functional brain connectivity (fcMRI) during painful stimulation. As reliability informs the validity of research findings, it is imperative to examine, especially given recent emphasis on using functional neuroimaging as a tool for biomarker development. Although proposed pain neural signatures have been derived using complex, multivariate algorithms, even the reliability of less complex fcMRI findings has yet to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
(44 reference statements)
1
16
0
Order By: Relevance
“…We previously examined test-retest reliability of functional MRI data compared with self-report in a highly-controlled, experimental design and found that these data did not outperform the reliability of participants’ pain ratings. 15,16 This finding suggests that inherent assumptions about the reproducibility of neuroimaging findings over time are inadequate. Future studies should examine test-retest reliability and specificity of particular brain regions and connections of proposed markers to determine their robustness and relationship to clinical end points over time.…”
Section: Discussionmentioning
confidence: 99%
“…We previously examined test-retest reliability of functional MRI data compared with self-report in a highly-controlled, experimental design and found that these data did not outperform the reliability of participants’ pain ratings. 15,16 This finding suggests that inherent assumptions about the reproducibility of neuroimaging findings over time are inadequate. Future studies should examine test-retest reliability and specificity of particular brain regions and connections of proposed markers to determine their robustness and relationship to clinical end points over time.…”
Section: Discussionmentioning
confidence: 99%
“…The researcher asked the patients, “On a 0–10 scale, how severe has been the worst pain that you have experienced within the last week?” In the follow-up sessions, the researcher again asked about the pain. The VAS has excellent test-retest reliability (ICC = 0.95; Letzen, Boissoneault, Sevel, & Robinson, 2016) and adequate concurrent validity ( r = −.60 with the Pain degree subscale of Larson Knee Scale; Flandry et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…A neuroimaging-derived biomarker cannot be reliably used for scientific or clinical purposes if the measures composing it do not demonstrate high test-retest reliability (i.e., the reproducibility of results over time). This concern is especially relevant given recent evidence that the test-retest reliability of functional connectivity metrics may vary widely depending on the brain regions examined [19•]. For this reason, the reliability of neuroimaging-based measures should not be taken for granted.…”
Section: Scientific and Clinical Utility Of Chronic Pain Biomarkersmentioning
confidence: 99%
“…These purported advantages have spurred interest in the development of biomarkers, although it is important to note that self-report remains the gold standard for pain measurement. Numerous studies have indicated that self-report measures of pain and psychosocial factors have excellent classification accuracy and reliability [8•, 19•, 20]. Indeed, evidence suggests that chronic pain patients can be distinguished from healthy controls with greater than 90% accuracy based on personality factors [21], perceived pain and functional disability [22], and simple visual analog scale (VAS) measures of affect [23••].…”
Section: Introductionmentioning
confidence: 99%